The Effect of Using Hormonal Contraception on the Incidence of Breast Cancer - Yermi, Yermi; Adam, Adriyani; Ningsih, Eka Sarofah; Iriani, Restu; Surya, Sara; Rukayah, Siti (International Journal of Health Sciences, 2023)
Cancer is a cell that has lost its normal control and mechanism, resulting in irregular growth. Cancer can occur from various tissues in various organs in line with the growth and development of cancer cells - cancer cells form a mass of malignant tissue that infiltrates nearby tissues and can spread (mentastasis) throughout the body. The purpose of this study was to determine the effect of hormonal contraceptive use on the incidence of breast cancer in patients at Dr. Wahidin Sudirohusodo Ujung Pandang Hospital Makassar. This research method is observational research with case control study design. Where case control is an analytic study that concerns how risk factors are studied using a retrospective approach. The results obtained Odds ratio value = 0.75. In addition, it was also obtained a lower limit value of 0.36% and an upper limit value of 1.38 at a 95% confidence level (95% C1). Conclusion that the use of hormonal contraceptive is not an influence on the incidence of breast cancer (large OR: 0.42 with a lower limit value of 0.17 and an Upper limit value of 2.50) is a protective factor for the incidence of breast cancer.